Sosialisasi Go-Green di SD Negeri Ngino: Bersama Lestarikan Alam, Menjadikan Sekolah Tempat yang Aman dan Nyaman - Azizah, Shela Rahma; Nobyyandi, Faisal; Rohman, Muhsin Fathar; Setiawan, Yoga; Ibad, Mohammad Nasaikhul; Sholeha, Sinta Mar’atus; Rochmania, Naila; Aula, Ifadatul; Putri, Jivinda Margareta Kristina; Hasanah, Lailatul; Faizah, Nisa Nur; Salsabila, Wanda Syeilina; Jannah, Syifa Nur; Hardiningrum, Rita Ayu Tri; Rahmawati , Salsabilla Ditya; Zamzami, Fieki Hilyah; Fanani, Moh. Zainal (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The Go-Green socialization program at SD Negeri Ngino aims to increase students' awareness and concern for environmental conservation. This program involves tree planting activities, waste management, and education about the importance of a clean and green environment. Through the ABCD (Asset-Based Community Development) method, this program is carried out collaboratively with the school, starting from observation to the implementation of activities. The results obtained show an increase in students' understanding of the Go-Green concept and its application in daily life. Thus, this program is expected to be a solution to school environmental problems and create a safe, comfortable, and supportive learning environment.